Implementasi Manajemen Mutu Terpadu Dalam Meningkatkan Mutu Lulusan Di SMP IT Wahdatul Ummah Kota Metro - HASAN, MUSTAQIM; Andi Warisno; Nasruddin Harahap; Nurul Hidayati Murtafiah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
This article will discuss the problems faced in implementing the implementation of integrated quality management in SMP IT Wahdatul Ummah Metro City in improving the quality of graduates. The purpose of this study is to develop an effective quality management system starting from planning, implementation and evaluation to improve the quality of graduates at the IT Wahdatul Ummah Middle School in Metro City. This qualitative research was conducted through interviews with a sample of participants. The goal is to gain a better understanding of their experiences with mental illness. This research includes data on principals, vice principals for curriculum, vice principals for student affairs, teachers, and students. Data collection techniques used in this study were interviews and documentation. Both methods provide valuable information that can be used to improve the quality of life of residents in a particular area. Another way to check the validity of data is to use source triangulation. This can be done by looking at different sources of information to see if they support each other. If data is found to be invalid, it may need to be revised or completely rewritten. Data analysis in this study includes triangulation and reference materials. Triangulation is a data analysis method that uses various sources of information to form a more accurate picture. Reference materials are documents or sources of information that can be used to help corroborate or support data analysis. this study found that the implementation of integrated quality management can improve the achievement of school goals starting from the planning, implementation, and evaluation stages are all important aspects of this process. Setting the school's vision, mission and goals is an important part of improving student achievement and the quality of graduates. Programs and activities must be oriented and focused on improving student achievement and meeting customer needs and satisfaction. Continuous improvement in all areas of the school's services is essential to ensure that the school remains focused on its goals.